Human lung epithelial cells support human metapneumovirus persistence by overcoming apoptosis. Issue 2 (6th March 2018) - Marsico, Stefania; Caccuri, Francesca; Mazzuca, Pietro; Apostoli, Paola; Roversi, Sara; Lorenzin, Giovanni; Zani, Alberto; Fiorentini, Simona; Giagulli, Cinzia; Caruso, Arnaldo
Abstract: Human metapneumovirus (hMPV) has been identified as a major cause of lower respiratory tract infection in children. Epidemiological and molecular evidence has highlighted an association between severe childhood respiratory viral infection and chronic lung diseases, such as asthma and chronic obstructive pulmonary disease. Currently, animal models have demonstrated the ability of hMPV to persist in vivo suggesting a role of the virus in asthma development in children. However, mechanisms involved in hMPV persistence in the respiratory tract are not yet understood. In the present study we monitored hMPV infection in human alveolar epithelial A549 cells in order to understand if the virus is able to persist in these cells upon acute infection. Our data show that hMPV initially induces an apoptotic process in A549 cells through poly (ADP-ribose) polymerase 1 cleavage, caspase-3/7 activation and Wee1 activity. The hMPV-infected cells were then able to overcome the apoptotic pathway and cell cycle arrest in G2/M by expressing B-cell lymphoma 2 and to acquire a reservoir cell phenotype with constant production of infectious virus. These findings provide evidence of the ability of hMPV to persist in alveolar epithelial cells and help in understanding the mechanisms responsible for hMPV persistence in the human respiratory tract. Abstract : Down-modulation of the apoptotic pathway leads to a persistent replication of human metapneumovirus in human lung epithelial cells.